Cost analysis for sustainable off-site construction based on a multiple-case study in China - Mao, C.; Xie, F.; Hou, L.; Wu, Peng; Wang, J.; Wang, Xiangyu (Elsevier, 2016)
Off-site construction (OSC) methods, such as prefabrication and modularisation have been regarded as an efficient way to boost sustainability and productivity against conventional cast-in-situ methods. Nevertheless, the promotion of OSC in many countries has lagged behind during the past 20 years because of the lack of explicit recognition with regard to the spending and savings associated with deploying such innovative methods in the construction industry. The multiple-case study method is applied to conduct an in-depth analysis on expenditure items of implementing OSC against conventional construction methods in China. Findings validate that the total cost of implementing OSC or semi-OSC techniques is significantly higher than that for conventional construction methods. The major expenses are incurred from such processes as prefabricated component production, transportation, and design consultancy. Compared with developed countries, the experience, skills, and market demand of applying OSC in China are far from adequate, which also increases the price of deploying OSC nationwide. By contrast, the spending of OSC on masonry, plastering, and measurement works is lower. Furthermore, a shift from on-site construction to factory-based indoor prefabrication decreases the number of workers required and the project delivery timeframe, thereby contributing to cost savings. To conclude, this study rationalises the wider adoption of OSC in the near future through comprehensive and thorough cost analysis case studies from which stakeholders in China would understand the pros and cons of OSC and eventually make deliberate decisions.